ANALYSIS OF THE APPLICATION OF THE TECHNOLOGY OF WATER AND GAS IMPACT ON THE FORMATIONS WITH THE PRESENCE OF A GAS CAP FOR INCREASING OIL RECOVERY AND UTILIZATION OF LOW-PRESSURE ASSOCIATED GAS ON THE EXAMPLE OF THE FIELDS OF WESTERN SIBERIA - Pavel N. Zyatikov; Ruslan F. Mazitov; Pavel V. Volkov; Natalia P. Zakharova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2022)
The relevance of the study is caused by the fact that at present there are practically no pure oil fields left on the territory of Western Siberia. A huge share of reserves is concentrated in oil rims, reservoirs with high gas pressure or the presence of a gas cap. The development of such oil fields by simple methods (for example, a rigid water pressure mode) is difficult, since there is a sharp decrease in reservoir pressure on them and the impossibility of its recovery by these mechanisms. It is necessary to consider alternative methods of influence to involve hard-to-recover hydrocarbon reserves in the development. The article discusses the combined use of water-gas treatment with the utilization of associated oil gas. The technique is caused by the fact that, first of all, a mechanism for gas compression and mixing with liquid has been developed to maintain reservoir pressure. The joint methodology of water-gas impact will allow effectively influencing reservoir with high gas pressure, and will also eliminate the need for utilization of associated oil gas due to technological processes. The main aim is to research and suggest a method for using water-gas impact with the recycling of associated oil gas for areas with a rate of reservoir pressure drop. Object: reservoir with high gas content under development. Methods: theoretical methods to substantiate the way of increasing gas pressure and the ability to mix gas with liquid to maintain reservoir pressure, analytical and computational methods. Results. The authors obtained the technique for compressing and mixing associated oil gas. The paper considers the technique for applying water-gas treatment using software. The effectiveness of the method was proved.